2018
DOI: 10.14434/josotl.v18i4.22784
|View full text |Cite
|
Sign up to set email alerts
|

Active University Teaching and Engaged Student Learning: A Mixed Methods Approach

Abstract: The purpose of this research was to examine how learning space design and implementation of an active learning pedagogy based on the 5E Instructional Model influence university faculty’s teaching practices and students’ engagement. Faculty Fellows were recruited from a public, medium-sized university in the United States to teach courses, typically taught in a traditional classroom setting, in a new Active Learning Center (ALC) classroom.  The classroom was funded by a Steelcase® Education Active Learning Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This data corroborates that the teaching-learning strategies used in the classroom play a fundamental role in student performance, showing a direct relationship with engagement levels [104,110,111] and how implementing these strategies in the classroom leads to better student satisfaction and performance data [112]. Numerous studies highlight the positive impact of student-centered learning strategies such as flipped classrooms, problem-solving, and case studies, among others, improving students' class participation and cognitive attention [113,114], a perception teachers and students share [115]. These studies are of great value from an applied point of view, as they provide scientific support for the need to orient university teaching in the classroom towards didactic methodologies that enhance specific elements that generate engagement.…”
Section: Discussionsupporting
confidence: 71%
“…This data corroborates that the teaching-learning strategies used in the classroom play a fundamental role in student performance, showing a direct relationship with engagement levels [104,110,111] and how implementing these strategies in the classroom leads to better student satisfaction and performance data [112]. Numerous studies highlight the positive impact of student-centered learning strategies such as flipped classrooms, problem-solving, and case studies, among others, improving students' class participation and cognitive attention [113,114], a perception teachers and students share [115]. These studies are of great value from an applied point of view, as they provide scientific support for the need to orient university teaching in the classroom towards didactic methodologies that enhance specific elements that generate engagement.…”
Section: Discussionsupporting
confidence: 71%
“…Grounded in Constructivist theory, the 5E Instructional model places the student at the centre of knowledge building, while instructors facilitate interaction with content and guide the inquiry process (Bybee et al, 2006). Offering a research-based, sequential framework that provides a conceptual-change model of learning (Bybee & Landes, 1990;Sengul & Schwartz, 2020), empirical studies have shown that the 5E instructional model significantly impacts student engagement and instructional effectiveness (Sengul & Schwartz, 2020;Tanner, 2010;Wheat et al, 2018). Research also indicates that active learning experiences are a very significant contributor to college student achievement and retention (Sengul & Schwartz, 2020).…”
Section: Pedagogymentioning
confidence: 99%
“…In the elaboration phase students apply concepts learned to new or unique scientific problems. Instruction focuses on presenting students with a novel challenge that requires them to apply and extend the concepts mastered in prior phases (Sengul & Schwartz, 2020;Wheat et al, 2018). In the third semester of this course, the students test and calibrate their experiments.…”
Section: Elaboratementioning
confidence: 99%
“…According to Doi (2016), positive experience can facilitate individuals’ engagement with the task or activity. Some researchers, such as Lin (2020) and Wheat et al (2018), have explained the likelihood of stimulating individuals’ engagement through the contextual features of an environment and attributes of student experience in a learning context. This leads us to argue that individuals’ experience may directly and indirectly influence their engagement in online environments.…”
Section: Literature Reviewmentioning
confidence: 99%